The Impact of Compressed Workweek on Absenteeism: The Case of Ontario Prison Guards on a Twelve-hour Shift - Venne, Rosemary (Relations industrielles / Industrial Relations, 1997)
The study consists of absenteeism measures for a group of prison guards who switched from an 8-hour work day to a 12- hour day compressed workweek (CWW) schedule with absenteeism measures for one year prior to the onset of the schedule and two years on the new schedule. Absenteeism data were compared between the CWW group and a comparison group of regular schedule guards and between the pre-CWW and CWW periods. Absenteeism leuels were higher for the CWW group compared to the comparison group, and were higher over the CWW period when compared to the pre-CWWperiod. In the best specified models, those guards on the CWW had higher absenteeism than the comparison group, though the latter difference was not statistically significant.